When Two Become One? Examining Kamala Harris and Joe Biden's Campaign Themes from Primary to General Election. (Presidential Studies Quarterly, 2022)
Moving from primary opponents to presidential ticket partners requires negotiation and strategy. Yet no work has systematically tracked the evolution of how two separate campaigns rhetorically become one. Rooted in partisan appeals, descriptive and policy representation, and ticket balancing research, this study employs two computer‐assisted content analytic methods to Kamala Harris and Joe Biden's tweets during the 2020 U.S. presidential primary and general election. Shifting between campaign phases, Harris did not rhetorically engage in ticket balancing or emphasize her qualifications, favoring other techniques instead to support Biden. Biden's messaging remained largely consistent yet showed some accommodations to emerging contexts.